Kerangka Kerja Inovasi Digital untuk Organisasi Skala Kecil: Integrasi Teori dan Praktik - Marcel, Marcel; Pratama, Dimas W.; Aotearoa, Garpepi H. (STMIK Palangkaraya, 2024)
This research proposes a framework designed to support digital innovation in small-scale organizations often constrained by limited resources and knowledge. This framework is built based on theoretical knowledge, which comes from literature reviews, and practical knowledge, which comes from focus group discussions involving several experts. The framework includes nine key processes: Leadership Commitment and Support; Culture of Innovation and Risk Tolerance; Cross-Functional Collaboration and Diversity; Agile and Flexible Process; Integration and Utilization of Digital Technology; Knowledge Sharing and Continuous Learning; Allocation of Resources for Innovation; External Engagement and Open Innovation; Performance Evaluation and Feedback. These processes were developed to be interrelated and form a comprehensive approach to fostering an innovative environment. In addition, this framework also integrates the ADKAR, a change management model, to facilitate the practical application of this framework in organizations. The existence of limited resources and knowledge in small-scale organizations demands particular strategies in adopting the framework, including more strategic resource allocation, intensive training for skill development, and collaboration with external institutions to support technology and innovation needs.